1994
DOI: 10.1021/bi00199a003
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Hydrogen Bonding in Enzyme-Substrate Complexes of Chloramphenicol Acetyltransferase by Infrared Spectroscopy and Site-Directed Mutagenesis

Abstract: Chloramphenicol acetyltransferase (CAT) reversibly transfers an acetyl group between CoA and the 3-hydroxyl of either chloramphenicol (Cm) or 1-acetylchloramphenicol (1AcCm). The products of the forward reactions, 3-acetylchloramphenicol (3-AcCm) and 1,3-diacetylchloramphenicol (1,3Ac2-Cm), are the substrates for the reverse reaction. The role of the 3-acetyl carbonyl group in the binding of the substrates 3AcCm and 1,3Ac2Cm to CAT has been investigated using infrared spectroscopy. Comparison of difference spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 26 publications
(35 reference statements)
1
6
0
Order By: Relevance
“…From a methodological point of view, we demonstrate that competition experiments can be performed in the infrared spectral region, from which relative dissociation constants can be obtained without the need to develop a binding assay, and confirm that different binding modes of ligands can be detected as shown before (White and Wharton, 1990;Murray et al, 1994;Ryan and Baenziger, 1999;and reviewed in Wharton, 2000). Applications like this will soon gain importance in fundamental and applied research when mixing devices become commercially available that makes these experiments just as easy to perform in the infrared spectral region as in the visible spectral range.…”
Section: Discussionsupporting
confidence: 69%
“…From a methodological point of view, we demonstrate that competition experiments can be performed in the infrared spectral region, from which relative dissociation constants can be obtained without the need to develop a binding assay, and confirm that different binding modes of ligands can be detected as shown before (White and Wharton, 1990;Murray et al, 1994;Ryan and Baenziger, 1999;and reviewed in Wharton, 2000). Applications like this will soon gain importance in fundamental and applied research when mixing devices become commercially available that makes these experiments just as easy to perform in the infrared spectral region as in the visible spectral range.…”
Section: Discussionsupporting
confidence: 69%
“…Compounds 6 , 14 , 15 and 16 , lacking the acetate moiety at C13 hydroxyl group, suffer a paulic acid migration to that position, thus becoming shunt products: 6-hydroxyl-13- O -paulyl-paulinone ( 6′ ), 13- O -deacetyl-13- O -paulyl-paulomycin E ( 14′ ), 13- O -deacetyl-13- O -paulyl-paulomycin B ( 15′ ) and 13- O -deacetyl-13- O -paulyl-paulomycin A ( 16′ ). Migration of acyl groups in aqueous solutions has been demonstrated to occur in other compounds such as betacyanins where glucose 6′- O -position is always favored [ 43 ], thuggacins that suffer acyl migrations of their lactone group [ 44 ], and chloramphenicol that undergoes an intra molecular rearrangement of an acetyl group from 3-hydroxyl to 1-hydroxyl group [ 45 ]. It has been demonstrated that acyl migration occurs to primary hydroxyl groups, which is the most stable position for acyl moieties [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Preparation of 3-Acetyl-Cm. 3-Acetyl-Cm was made and purified by the procedure described by Murray et al (1994).…”
Section: Methodsmentioning
confidence: 99%
“…Much is now known of the interaction of CAT and its substrates from (a) crystallographic studies of the binary complexes of enzyme and Cm or CoA at 1.75 and 2.4 A resolution, respectively (Leslie, 1990;Leslie et al, 1988) and (b) results of spectroscopic experiments (fluorescence, NMR, and IR) with CAT and its ligands in conjunction with structure-based mutagenesis (Ellis et al, 1991;Derrick et al, 1992;Murray et al, 1994). The choice of protein for the above studies, as well as for those described here, has been the type III enzyme (CATm) which is not only the sole naturally occurring CAT variant to yield diffraction quality crystals but is also the most competent catalytically.…”
mentioning
confidence: 99%